Negative active material, preparation method thereof and related device

By covering polymethyl methacrylate and other substances on the surface of the negative electrode active material of the lithium-ion battery, forming a coating of appropriate thickness, the irreversible consumption problem caused by the interface reaction of the lithium-ion battery is solved, and the cycling performance of the battery is improved and the Kulun is improved. efficiency.

CN119170755AActive Publication Date: 2024-12-20CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202310732590.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2024-12-20
Estimated Expiration
2043-06-20

AI Technical Summary

Technical Problem

During the circulation process, lithium-ion batteries cause excessive irreversible consumption of lithium ions due to interface reactions, which affects the battery's cycle stability and Coulomb efficiency.

Method used

The surface of the negative electrode active material is coated with a coating of polymethyl methacrylate, sodium maleate and diethanolamide borate, with a thickness of 5nm-50nm. The coating is formed by polymerization to reduce interface reactions and improve interfacial reactions and Lithium ion deintercalation efficiency.

Benefits of technology

It significantly improves the cycle performance of the battery and the first-circle Coulomb efficiency, reduces the consumption of irreversible active ions, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170755A_ABST
    Figure CN119170755A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a negative electrode active material, a preparation method thereof and a related device. The negative electrode active material comprises a negative electrode active material and a coating layer, the coating layer coats the surface of the negative electrode active material, and the coating layer comprises at least one of polymethyl methacrylate, sodium maleate and oleic diethanolamide borate. According to the technical scheme, the cycle performance and the first-circle coulombic efficiency of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and more specifically, to a negative electrode active material and a preparation method thereof, a negative electrode sheet, a battery cell, a battery and an electrical device. Background Art

[0002] In recent years, lithium-ion batteries have been used in more and more fields, such as wind power, hydropower, thermal power generation, solar cells and other energy storage power sources, as well as electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. While lithium-ion batteries have made great progress, better requirements have been put forward for their performance in all aspects.

[0003] Therefore, how to improve the performance of lithium-ion batteries is an urgent problem to be solved. Summary of the invention

[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a negative electrode active material and its preparation method, a negative electrode plate, a battery cell, a battery and an electrical device, which improve the cycle performance and the first-cycle coulomb efficiency of the battery.

[0005] The first aspect of the present application provides a negative electrode active material, comprising: a negative electrode active substance and a coating layer, wherein the coating layer is coated on the surface of the negative electrode active substance, and the coating layer comprises at least one of polymethyl methacrylate, sodium maleate and oleic acid diethanolamide borate.

[0006] In the embodiment of the present application, the negative electrode active material includes a negative electrode active material and a coating layer, the coating layer is coated on the surface of the negative electrode active material, and the coating layer includes at least one of polymethyl methacrylate, sodium maleate and oleic acid diethanolamide borate. By coating a coating layer on the surface of the negative electrode active material, the coating layer includes at least one of polymethyl methacrylate, sodium maleate and oleic acid diethanolamide borate, such a coating layer has a flexible property, which can not only reduce the damage to the material structure of the coating layer caused by multiple conduction of lithium ions, but also inhibit the interface reaction between the electrolyte and the surface of the negative electrode plate, reduce the consumption of irreversible active ions and improve the efficiency of lithium ion deintercalation, thereby improving the first cycle coulomb efficiency and cycle performance of the battery.

[0007] In a possible implementation manner, the coating layer has a thickness of 5 nm-50 nm. Optionally, the coating layer has a thickness of 10 nm-20 nm.

[0008] In the embodiment of the present application, if the coating layer is too thin, the coating layer does not sufficiently coat the negative electrode active material, and its effect on inhibiting the negative electrode interface reaction is not obvious; if the coating layer is too thick, it will affect the transmission rate of lithium ions. Therefore, by making the coating layer 5nm-50nm thick, especially 10nm-20nm, it helps to further improve the cycle performance and first cycle coulomb efficiency of the battery.

[0009] In a possible implementation, the molecular weight of the polymethyl methacrylate is 500,000-2,000,000. Optionally, the molecular weight of the polymethyl methacrylate is 1,000,000-1,500,000.

[0010] In the embodiment of the present application, methyl methacrylate and the negative electrode active material are polymerized to form a negative electrode active material including a negative electrode active material and a coating layer. This preparation method is simple and has abundant raw materials, which is conducive to wide application in industrial production. In addition, the molecular weight of polymethyl methacrylate is 500000-2000000, especially 1000000-1500000, and polymethyl methacrylate with a higher degree of polymerization is used as the coating layer of the negative electrode active material, which is conducive to the coating layer to fully exert its function.

[0011] In a possible embodiment, the negative electrode active material includes at least one of graphite and silicon-based materials. Optionally, the silicon-based material includes at least one of elemental silicon, silicon oxide compounds, silicon carbon compounds, silicon nitrogen compounds, and composites of elemental silicon, silicon oxide compounds, and silicon carbon compounds. Optionally, the silicon oxide compound includes Si a O b , wherein a=1, 1≤b≤2; Optionally, the silicon carbon compound comprises Si c C d , where c=1, d=1.

[0012] In the embodiment of the present application, at least one of graphite and silicon-based materials is used as the negative electrode active material, and further, at least one of elemental silicon, silicon oxide compounds, silicon carbon compounds, silicon nitrogen compounds, and composites of elemental silicon, silicon oxide compounds, and silicon carbon compounds is used, and further, Si a O b 、Si c C d At least one of the following, where a=1, 1≤b≤2, c=1, and d=1, is used as a negative electrode active material to help improve the energy density of the battery.

[0013] The second aspect of the present application provides a method for preparing a negative electrode active material, comprising: providing a negative electrode active substance and a coating substance; mixing the negative electrode active substance and the coating substance, and treating them to obtain the negative electrode active substance and a coating layer coated on the surface of the negative electrode active substance; wherein the coating substance includes at least one of methyl methacrylate, sodium maleate and oleic acid diethanolamide borate.

[0014] In the embodiment of the present application, after the negative electrode active material and the coating material are mixed and treated, a negative electrode active material including the negative electrode active material and a coating layer coated on the surface of the negative electrode active material can be obtained; wherein the coating material includes at least one of methyl methacrylate, sodium maleate and oleic acid diethanolamide borate. The negative electrode active material prepared by the preparation method can make the battery including the negative electrode active material have good cycle performance and first cycle coulomb efficiency.

[0015] In a possible implementation manner, the coating layer has a thickness of 5 nm-50 nm. Optionally, the coating layer has a thickness of 10 nm-20 nm.

[0016] In the embodiments of the present application, by making the thickness of the coating layer 5nm-50nm, especially 10nm-20nm, it helps to further improve the cycle performance and the first-cycle coulombic efficiency of the battery.

[0017] In a possible implementation, the methyl methacrylate is polymerized to form the coating layer, and the coating layer includes polymethyl methacrylate; wherein the molecular weight of the polymethyl methacrylate is 500,000-2,000,000, and optionally, the molecular weight of the polymethyl methacrylate is 1,000,000-2,000,000.

[0018] In the embodiment of the present application, a coating layer is formed by polymerizing methyl methacrylate to form a negative electrode active material including a negative electrode active substance and a coating layer. This preparation method is simple and has abundant raw materials, which is conducive to wide application in industrial production. In addition, the molecular weight of polymethyl methacrylate is 500000-2000000, and polymethyl methacrylate with a high degree of polymerization is used as a coating layer of the negative electrode active substance, which is conducive to the coating layer to fully exert its function.

[0019] In a possible implementation manner, the mass ratio of the methyl methacrylate to the negative electrode active material is 1-5. Optionally, the mass ratio of the methyl methacrylate to the negative electrode active material is 1.5-3.

[0020] In the embodiment of the present application, the different mass ratios of the negative electrode active material and methyl methacrylate directly affect the thickness of the coating layer. Therefore, by making the mass ratio of methyl methacrylate to the negative electrode active material 1-5, especially 1.5-3, the coating layer can have a more reasonable thickness, thereby exerting the effect of the coating layer.

[0021] In a possible implementation, the treatment temperature of the negative electrode active material and the methyl methacrylate is not less than 60°C. Optionally, the treatment temperature is 60°C-220°C.

[0022] In the embodiment of the present application, methyl methacrylate is polymerized to form polymethyl methacrylate, and polymethyl methacrylate is used as a coating layer to coat the negative electrode active material. If the processing temperature is too low, the polymerization of polymethyl methacrylate may fail; if the processing temperature is too high, it will affect the relative molecular weight of polymethyl methacrylate, resulting in a decrease in the performance of polymethyl methacrylate. Therefore, by maintaining the processing temperature of the negative electrode active material and methyl methacrylate at not less than 60°C, especially at 60°C-220°C, the polymethyl methacrylate formed by polymerization has better performance, which helps to further improve the performance of the battery.

[0023] In a possible implementation manner, the negative electrode active material and the methyl methacrylate are treated for 1 hour to 8 hours. Optionally, the treatment time is 3 hours to 5 hours.

[0024] In the embodiments of the present application, by maintaining the treatment time of the negative electrode active material and methyl methacrylate at 1 h-8 h, especially at 3 h-5 h, the polymethyl methacrylate can have a reasonable thickness, thereby improving the battery performance.

[0025] In a possible implementation, the catalyst, the negative electrode active material and the methyl methacrylate are mixed. Optionally, the catalyst includes at least one of an organic peroxide and an azo compound.

[0026] In the embodiment of the present application, a catalyst is added to the reaction between methyl methacrylate and the negative electrode active material, and the catalyst can reduce the activation energy of the polymerization reaction and accelerate the polymerization reaction. Therefore, by adding a catalyst during the polymerization of polymethyl methacrylate, and the catalyst can be at least one of an organic peroxide and an azo compound, the generation of polymethyl methacrylate can be accelerated.

[0027] In a possible embodiment, the coating material includes at least one of sodium maleate and oleic acid diethanolamide borate; the treatment temperature of the negative electrode active material and at least one of sodium maleate and oleic acid diethanolamide borate is not less than 40°C, and optionally, the treatment temperature is 40°C-120°C.

[0028] In the embodiment of the present application, a negative electrode active material including a negative electrode active material and a coating layer can be obtained by mixing the negative electrode active material with sodium maleate or oleic acid diethanolamide borate, and the processing temperature of the two is maintained at not less than 40°C, especially 40°C-120°C, so as not to destroy the activity of the coating layer, thereby improving the performance of the battery.

[0029] In a possible implementation, the mass ratio of at least one of the sodium maleate and the oleic acid diethanolamide borate to the negative electrode active material is 1-3. Optionally, the mass ratio of at least one of the sodium maleate and the oleic acid diethanolamide borate to the negative electrode active material is 1-2.

[0030] In the embodiment of the present application, when at least one of sodium maleate and oleic acid diethanolamide borate is used as a coating layer to coat the negative electrode active material, the two need only be directly mixed at a certain temperature. By making the mass ratio of at least one of sodium maleate and oleic acid diethanolamide borate to the negative electrode active material 1-3, especially 1-2, the coating layer can have a suitable thickness to improve the performance of the battery.

[0031] In a possible embodiment, the negative electrode active material includes at least one of graphite and silicon-based materials. Optionally, the silicon-based material includes at least one of elemental silicon, silicon oxide compounds, silicon carbon compounds, silicon nitrogen compounds, and composites of elemental silicon, silicon oxide compounds, and silicon carbon compounds. Optionally, the silicon oxide compound includes Si a O b , wherein a=1, 1≤b≤2; Optionally, the silicon carbon compound comprises Si c C d , where c=1, d=1.

[0032] The third aspect of the present application provides a negative electrode plate, comprising the negative electrode active material described in any one of the embodiments of the first aspect, and / or comprising the negative electrode active material prepared by the preparation method of the negative electrode active material described in any one of the embodiments of the second aspect.

[0033] A fourth aspect of the present application provides a battery cell, comprising the negative electrode plate described in the third aspect.

[0034] A fifth aspect of the present application provides a battery, comprising the battery cell described in the fourth aspect.

[0035] The sixth aspect of the present application provides an electrical device, comprising the battery described in the fifth aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0037] Figure 1 A schematic diagram of the structure of a negative electrode active material according to an embodiment of the present application;

[0038] Figure 2 TEM image of the negative electrode active material according to one embodiment of the present application;

[0039] Figure 3 A flow chart of the preparation of a negative electrode active material according to an embodiment of the present application;

[0040] Figure 4 A schematic diagram of a battery cell according to an embodiment of the present application;

[0041] Figure 5 A schematic structural diagram of a battery cell according to another embodiment of the present application;

[0042] Figure 6 A schematic diagram of a battery according to an embodiment of the present application;

[0043] Figure 7 A schematic diagram of the structure of a battery according to one embodiment of the present application;

[0044] Figure 8 It is a schematic structural diagram of an electrical device according to one embodiment of the present application. DETAILED DESCRIPTION

[0045] The following describes in detail the negative electrode active material and preparation method thereof, negative electrode sheet, battery cell, battery and electric device of the present application with appropriate reference to the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually the same structure may be omitted. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0046] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a specific range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0047] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0048] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0049] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, and can be performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0050] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or comprised.

[0051] The terms "above", "below", "greater than" or "less than" as used in this application include the number, for example, "at least one" means one or more, and "at least one of A and B" means "A", "B" or "A and B".

[0052] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0053] The cycle life of lithium batteries is related to the stability of the interface (such as the interface between the electrode plate and the electrolyte). The formation of the interface is often accompanied by the irreversible consumption of lithium ions, especially the interface between the negative electrode plate and the electrolyte. Because when the battery is charged and discharged for the first time, the solid electrolyte interface (SEI) film formed will consume a large amount of lithium ions, and this part of the consumed lithium ions is irreversible. If too many lithium ions are consumed, it will have a greater impact on the performance of the battery. Therefore, how to reduce the irreversible consumption of limited lithium ions is the key to restricting the cycle stability and coulomb efficiency of lithium batteries.

[0054] In order to solve the above problems, on the one hand, active lithium can be supplemented, such as adding lithium supplement materials or constructing lithium supplement structures in the battery, but lithium supplement materials are generally highly active and require high processing conditions for the battery, and the possibility of industrialization is not high. On the other hand, the consumption of active lithium can be reduced, such as setting a polymer aluminum foil film layer on the surface of the negative electrode active material, but this method is complex and the possibility of industrialization is not high. Therefore, how to reduce the consumption of active lithium ions in a more direct way, thereby improving the cycle performance of the battery, is a problem that needs to be solved urgently.

[0055] In view of this, the present application provides a negative electrode active material and a preparation method thereof, wherein the negative electrode active material comprises: a negative electrode active material and a coating layer, wherein the coating layer is coated on the surface of the negative electrode active material, and the coating layer comprises at least one of polymethyl methacrylate, sodium maleate and oleic acid diethanolamide borate. By directly coating at least one of polymethyl methacrylate, sodium maleate and oleic acid diethanolamide borate on the surface of the substrate, the cycle performance and first cycle coulomb efficiency of a battery using the negative electrode active material can be improved.

[0056] The negative electrode active material and preparation method thereof, negative electrode sheet, battery cell, battery and electrical device of the present application are described below with reference to the accompanying drawings.

[0057] In addition, the technical solution of the present application is applicable to lithium-ion batteries or lithium metal batteries, and the present application does not limit this; for the convenience of description, the following description will take lithium-ion batteries as an example.

[0058] [Negative electrode active material]

[0059] Figure 1is a schematic diagram of the structure of the negative electrode active material according to one embodiment of the present application, Figure 2 TEM image of the negative electrode active material according to one embodiment of the present application. Figure 1 and Figure 2 As shown, the negative electrode active material 122 includes a negative electrode active material 1221 and a coating layer 1222 . The coating layer 1222 is coated on the surface of the negative electrode active material 1221 . The coating layer 1222 includes at least one of polymethyl methacrylate, sodium maleate and oleic acid diethanolamide borate.

[0060] Coating the surface of the negative electrode active material with at least one of polymethyl methacrylate, sodium maleate and oleic acid diethanolamide borate can improve the cycle performance and the first-cycle coulomb efficiency of the battery.

[0061] The coating here can be as follows Figure 1 The entire package shown can also be Figure 2 Partial wrap shown.

[0062] In the embodiment of the present application, the negative electrode active material includes a negative electrode active material 1221 and a coating layer 1222; further, the coating layer 1222 is coated on the surface of the negative electrode active material 1221, and the coating layer 1222 includes at least one of polymethyl methacrylate, sodium maleate and oleic acid diethanolamide borate. By coating a coating layer 1222 on the surface of the negative electrode active material 1221, and the coating layer 1222 includes at least one of polymethyl methacrylate, sodium maleate and oleic acid diethanolamide borate, such a coating layer 1222 has a flexible property, which can not only reduce the damage to the material structure of the coating layer 1222 caused by multiple conduction of lithium ions, but also inhibit the interface reaction between the electrolyte and the surface of the negative electrode plate 122, thereby reducing the consumption of irreversible active ions and improving the efficiency of lithium ion deintercalation, thereby improving the first cycle coulomb efficiency and cycle performance of the battery.

[0063] It should be noted that during the battery cycle, a solid electrolyte interface (SEI) film will be formed on the surface of the negative electrode plate 122. The coating layer 1222 is relatively close to the SEI film, so the coating layer 1222 can act as an "artificial" SEI film, forming a double SEI film with the SEI film formed by the battery, thereby inducing the generation of a more stable and thin SEI film.

[0064] The SEI film is a passivation layer formed on the surface of the active material when the active material and the electrolyte react at the solid-liquid interface during the initial charge and discharge process of the lithium-ion battery. The coating layer 1222 is an "artificial" SEI film, which means that it can play the role of a SEI film, but it is not a real SEI film.

[0065] In addition, it should be understood that the "lithium insertion" and "embedding" processes described in this application refer to the process in which lithium ions are embedded in the positive electrode active material or the negative electrode active material due to an electrochemical reaction, and the "extraction" and "de-intercalation" processes described in this application refer to the process in which lithium ions are extracted from the positive electrode active material or the negative electrode active material due to an electrochemical reaction.

[0066] In some embodiments, the thickness d1 of the coating layer 1222 is 5 nm-50 nm. Optionally, the thickness d1 of the coating layer is 10 nm-20 nm.

[0067] In the above scheme, if the coating layer 1222 is too thin, the coating layer 1222 does not sufficiently coat the negative electrode active material 1221, and the effect of suppressing the negative electrode interface reaction is not obvious; if the coating layer 1222 is too thick, the transmission rate of metal ions will be affected. Therefore, by making the thickness of the coating layer 1222 5nm-50nm, especially 10nm-20nm, it is helpful to further improve the cycle performance and the first cycle coulomb efficiency of the battery.

[0068] It should be noted here that the thickness of the coating layer can be 5 nm, 15 nm, 20 nm, 40 nm, or any value within the above range.

[0069] In some embodiments, the molecular weight of polymethyl methacrylate is 500,000-2,000,000. Optionally, the molecular weight of polymethyl methacrylate is 1,000,000-15,000,000.

[0070] In the embodiment of the present application, methyl methacrylate and negative electrode active material 1221 are polymerized to form negative electrode active material 122 including negative electrode active material 1221 and coating layer 1222. This preparation method is simple and has abundant raw materials, which is conducive to wide application in industrial production. In addition, the molecular weight of polymethyl methacrylate is 500000-2000000, especially 1000000-15000000. Polymethyl methacrylate with a higher degree of polymerization is used as coating layer 1222 of negative electrode active material 1221, which is conducive to the coating layer 1222 to fully exert its function.

[0071] It should be noted here that the molecular weight of polymethyl methacrylate can be 500,000, 800,000, 1,000,000, 1,500,000 or any value within the above range.

[0072] In addition, the molecular weight of polymethyl methacrylate will vary depending on its thickness.

[0073] In some embodiments, the negative electrode active material 1221 includes at least one of graphite and silicon-based materials. Optionally, the silicon-based material includes at least one of elemental silicon, silicon oxide compounds, silicon carbon compounds, silicon nitrogen compounds, and composites of elemental silicon, silicon oxide compounds, and silicon carbon compounds. Optionally, the silicon oxide compound includes Si a O b , wherein a=1, 1≤b≤2; Optionally, the silicon carbon compound includes Si c C d , where c=1, d=1.

[0074] In the above scheme, at least one of graphite and silicon-based materials is used as the negative electrode active material, and further, at least one of elemental silicon, silicon oxide compounds, silicon carbon compounds, silicon nitrogen compounds and composites of elemental silicon, silicon oxide compounds and silicon carbon compounds is used, and further, Si a O b 、Si c C d At least one of the following, where a=1, 1≤b≤2, c=1, and d=1, is used as a negative electrode active material to help improve the energy density of the battery.

[0075] The composite of elemental silicon, silicon oxide compound and silicon carbon compound may include composites formed by any two of these three, for example, it may be a multilayer composite structure formed by Si, SiO2 and C, namely Si@SiO2@C.

[0076] [Method for preparing negative electrode active material]

[0077] The second aspect of the present application provides a method for preparing a negative electrode active material. Figure 3 FIG. 1 is a flow chart of the preparation of the negative electrode active material according to one embodiment of the present application. Figure 3 As shown, the preparation method of the negative electrode active material includes:

[0078] S101, providing a negative electrode active material and a coating material;

[0079] S102, mixing the negative electrode active material and the coating material, and treating them to obtain the negative electrode active material and a coating layer coated on the surface of the negative electrode active material; wherein the coating material includes at least one of methyl methacrylate, sodium maleate and oleic acid diethanolamide borate.

[0080] The coating material is the material state before the coating layer treatment. If the coating material is methyl methacrylate, the coating layer finally formed is polymethyl methacrylate; if the coating material is sodium maleate and oleic acid diethanolamide borate, the coating layer is sodium maleate and oleic acid diethanolamide borate. Therefore, in the following text, sodium maleate and oleic acid diethanolamide borate can be referred to as coating material or coating layer, but methyl methacrylate cannot be referred to as coating layer, and polymethyl methacrylate cannot be referred to as coating material.

[0081] In the above scheme, after the negative electrode active material 1221 and the coating material are mixed and treated, the negative electrode active material 122 including the negative electrode active material 1221 and the coating layer 1222 coated on the surface of the negative electrode active material 1221 can be obtained; wherein the coating material includes at least one of methyl methacrylate, sodium maleate and oleic acid diethanolamide borate. The negative electrode active material 122 prepared by the preparation method can make the battery including the negative electrode active material 122 have good cycle performance and first cycle coulomb efficiency.

[0082] In some embodiments, the coating layer 1222 has a thickness of 5 nm to 50 nm. Optionally, the coating layer 1222 has a thickness of 10 nm to 20 nm.

[0083] In the above solution, by making the thickness of the coating layer 1222 5nm-50nm, especially 10nm-20nm, it helps to further improve the cycle performance and the first-cycle coulombic efficiency of the battery.

[0084] In some embodiments, methyl methacrylate is polymerized to form the coating layer 1222, and the coating layer 1222 includes polymethyl methacrylate; wherein the molecular weight of the polymethyl methacrylate is 500,000-2,000,000, and optionally, the molecular weight of the polymethyl methacrylate is 1,000,000-1,500,000.

[0085] Polymerization here refers to a polymerization reaction, which is the process of converting low molecular weight monomers into high molecular weight polymers.

[0086] In addition, before the process of polymerizing methyl methacrylate to form polymethyl methacrylate, methyl methacrylate can be directly mixed with the negative electrode active material 1221 , so that the negative electrode active material 122 having the coating layer 1222 can be directly formed.

[0087] In the above scheme, the coating layer 1222 is formed by polymerizing methyl methacrylate, and the negative electrode active material 122 including the negative electrode active material 1221 and the coating layer 1222 is formed. This preparation method is simple and has abundant raw materials, which is conducive to wide application in industrial production. In addition, the molecular weight of polymethyl methacrylate is 500000-2000000, and polymethyl methacrylate with a high degree of polymerization is used as the coating layer 1222 of the negative electrode active material 1221, which is conducive to the coating layer 1222 to fully exert its function.

[0088] In some embodiments, the mass ratio of methyl methacrylate to the negative electrode active material 1221 is 1-5. Optionally, the mass ratio of methyl methacrylate to the negative electrode active material 1221 is 1.5-3.

[0089] In the above scheme, the difference in the mass ratio of methyl methacrylate to the negative electrode active material 1221 directly affects the thickness of the coating layer 1222. Therefore, by making the mass ratio of methyl methacrylate to the negative electrode active material 1221 1-5, especially 1.5-3, the coating layer 1222 can have a more reasonable thickness, thereby exerting the effect of the coating layer 1222.

[0090] It should be noted here that the mass ratio of methyl methacrylate to the negative electrode active material 1221 can be 1.5, 2.8, 4.2, 5, or any value within the above range.

[0091] In some embodiments, the treatment temperature of the negative electrode active material 1221 and methyl methacrylate is not less than 60°C. Optionally, the treatment temperature is 60°C-220°C.

[0092] In the above scheme, methyl methacrylate is polymerized to form polymethyl methacrylate, and polymethyl methacrylate is used as a coating layer 1222 to cover the negative electrode active material 1221. If the processing temperature is too low, the polymerization of polymethyl methacrylate may fail; if the processing temperature is too high, it will affect the relative molecular weight of polymethyl methacrylate and reduce the performance of polymethyl methacrylate. Therefore, by keeping the processing temperature of the negative electrode active material 1221 and methyl methacrylate at not less than 60°C, especially at 60°C-220°C, the polymethyl methacrylate formed by polymerization has better performance, which helps to further improve the performance of the battery.

[0093] It should be noted here that the above-mentioned treatment temperature can be 60° C., 100° C., 150° C., 170° C., or any value within the above-mentioned range.

[0094] In some embodiments, the negative electrode active material 1221 and methyl methacrylate are treated for 1 hour to 8 hours. Optionally, the treatment time is 3 hours to 5 hours.

[0095] In the above scheme, by maintaining the treatment time of the negative electrode active material 1221 and methyl methacrylate at 1 h to 8 h, especially at 3 h to 5 h, better polymethyl methacrylate can be formed.

[0096] It should be noted here that the above-mentioned processing time can be 1.5h, 3h, 5h, 8h and any value within the above-mentioned range.

[0097] In some embodiments, a catalyst, negative electrode active material 1221 and methyl methacrylate are mixed. Optionally, the catalyst includes at least one of an organic peroxide and an azo compound.

[0098] A catalyst generally refers to a substance that increases the reaction rate without changing the total standard Gibbs free energy change of the reaction. It can also be described as a substance that can increase the chemical reaction rate without changing the chemical equilibrium in a chemical reaction, and whose mass and chemical properties do not change before and after the chemical reaction.

[0099] Organic peroxides refer to organic compounds containing -OO-peroxide functional groups formed by replacing the hydrogen atoms in hydrogen peroxide with organic groups such as alkyl, acyl, and aromatic groups, including but not limited to benzoic acid peroxide, methyl ethyl ketone peroxide, etc.

[0100] Azo compounds refer to compounds formed by connecting an azo group (─N=N─) with two hydrocarbon groups, with the general formula R─N=N─R, such as azobisisobutyronitrile.

[0101] In the above scheme, a catalyst is added to the reaction between methyl methacrylate and the negative electrode active material 1221. The catalyst can reduce the activation energy of the polymerization reaction and accelerate the polymerization reaction. Therefore, by adding a catalyst during the polymerization of polymethyl methacrylate, and the catalyst can be at least one of an organic peroxide and an azo compound, the generation of polymethyl methacrylate can be accelerated.

[0102] In some embodiments, the coating material includes at least one of sodium maleate and oleic acid diethanolamide borate; the treatment temperature of the negative electrode active material 1221 and at least one of sodium maleate and oleic acid diethanolamide borate is not less than 40°C, and optionally, the treatment temperature is 40°C-120°C.

[0103] In the above scheme, by mixing the negative electrode active material 1221 with sodium maleate or oleic acid diethanolamide borate, the negative electrode active material 122 including the negative electrode active material 1221 and the coating layer 1222 can be obtained. The processing temperature of the two is maintained at not less than 40°C, especially 40°C-120°C, so as not to destroy the activity of the coating layer 1222, thereby improving the performance of the battery.

[0104] It should be noted here that the above-mentioned treatment temperature can be 45° C., 60° C., 80° C., 100° C. and any value within the above-mentioned range.

[0105] In some embodiments, the mass ratio of at least one of sodium maleate and oleic acid diethanolamide borate to the negative electrode active material 1221 is 1-3. Optionally, the mass ratio of at least one of sodium maleate and oleic acid diethanolamide borate to the negative electrode active material 1221 is 1-2.

[0106] In the above scheme, when at least one of sodium maleate and oleic acid diethanolamide borate is used as the coating layer 1222 to coat the negative electrode active material 1221, the two can be directly mixed at a certain temperature. By making the mass ratio of at least one of sodium maleate and oleic acid diethanolamide borate to the negative electrode active material 1221 1-3, especially 1-2, the coating layer 1222 can have a suitable thickness to improve the performance of the battery.

[0107] It should be noted that the mass ratio of at least one of sodium maleate and oleic acid diethanolamide borate to the negative electrode active material 1221 can be 1.2, 1.5, 2, 3, or any value within the above range.

[0108] In some embodiments, the negative electrode active material 1221 includes at least one of graphite and a silicon-based material. Optionally, the silicon-based material includes Si a O b 、Si c C d At least one of the following, wherein a=1, 1≤b≤2, c=1, d=1, and optionally, the silicon-based material includes Si@SiO2@C.

[0109] It should be noted here that if graphite is used as the negative electrode active material 1221, it can be fresh graphite or waste graphite, that is, used graphite.

[0110] Typically, a battery cell includes a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive and negative electrodes. The electrolyte plays the role of conducting ions between the positive and negative electrodes. The separator is set between the positive and negative electrodes, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0111] It should be noted here that the “positive electrode sheet” and “negative electrode sheet” mentioned in the embodiments of the present application refer to the positive electrode sheet and the negative electrode sheet as a whole including active materials, current collectors or other additives.

[0112] [Negative electrode]

[0113] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material 122 .

[0114] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0115] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.), or a current collector that combines support capabilities with functional elements, such as carbon cloth, carbon film, carbonaceous, porous current collector, alloy modified current collector, and lithium-philic modified current collector.

[0116] In some embodiments, the negative electrode plate can be a rolled metal foil or a surface-coated inert layer of metal powder coated on a current collector; it can be a functional coated negative electrode, such as a carbon material coating (including single-arm, multi-arm conductive carbon tubes, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers, soft carbon and hard carbon, etc.), lithium-philic / sodium-philic metal composite coating, etc.

[0117] In some embodiments, the negative electrode plate is an alkali metal negative electrode. The alkali metal negative electrode may be an alkali metal layer pre-arranged on the surface of the current collector, or may be a negative electrode current collector, and an alkali metal layer is generated on the surface of the negative electrode current collector during the charge and discharge process. This application does not limit this.

[0118] In some embodiments, the negative electrode active material 1221 in the negative electrode active material 122 may also adopt negative electrode active materials for batteries known in the art. As an example, the negative electrode active material 1221 may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0119] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0120] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0121] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0122] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material 122, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0123] [Positive electrode]

[0124] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0125] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0126] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0127] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0128] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0129] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0130] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry, and the positive electrode slurry is coated on the positive electrode collector. After drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0131] [Electrolytes]

[0132] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0133] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0134] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0135] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0136] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0137] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0138] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0139] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 4 It is a schematic diagram of a battery cell according to an embodiment of the present application.

[0140] Figure 5 FIG. 1 is a schematic diagram of the structure of a battery cell according to another embodiment of the present invention. Figure 5 As shown, the outer packaging of the battery cell 100 includes a shell 11 and a cover plate 13. Among them, the shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 12 through a winding process or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the battery cell 100 can be one or more, and those skilled in the art can select according to specific actual needs.

[0141] In some embodiments, the battery cells 100 may also be assembled into a battery module. The battery module may contain one or more battery cells 100. The specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0142] Figure 6 is a schematic diagram of a battery according to one embodiment of the present application, Figure 7 This is a schematic diagram of the structure of a battery according to one embodiment of the present application. Figure 6 and Figure 7 The battery 400 may include a battery box and a plurality of battery cells 100 disposed in the battery box. The battery box includes an upper box body 401 and a lower box body 402. The upper box body 401 can cover the lower box body 402 and form a closed space for accommodating the battery cells 100. The plurality of battery cells 100 may be arranged in the battery box in any manner.

[0143] In addition, the present application also provides an electric device, which includes at least one of the battery cell 100 or the battery 400 provided in the present application. The battery cell 100 or the battery 400 can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0144] For example, Figure 8 Schematic diagram of the structure of an electric device according to an embodiment of the present application. Figure 8 As shown, the electrical device is a vehicle 1, and the vehicle 1 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A motor 500, a controller 600 and a battery 400 may be arranged inside the vehicle 1, and the controller 600 is used to control the battery 400 to supply power to the motor 500. For example, a battery 400 may be arranged at the bottom, front or rear of the vehicle 1. The battery 400 may be used to power the vehicle 1, for example, the battery 400 may be used as an operating power source for the vehicle 1, for the circuit system of the vehicle 1, for example, for the working power requirements during the start-up, navigation and operation of the vehicle 1. In another embodiment of the present application, the battery 400 may not only be used as an operating power source for the vehicle 1, but also as a driving power source for the vehicle 1, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1.

[0145] As the electric device, a battery cell 100 or a battery 400 may be selected according to its usage requirements.

[0146] The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the electric device's requirements for high power and high energy density of the battery, a battery cell 100 or a battery 400 may be used.

[0147] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and the battery cell 100 may be used as a power source.

[0148] [Example]

[0149] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0150] [Example 1]

[0151] 1). Preparation of lithium-ion batteries

[0152] 1.11). Preparation of negative electrode active material: Weigh the coating material methyl methacrylate (MMA) and the negative electrode active material graphite in a mass ratio of 3:1, and disperse them in 45 mL of deionized water, add catalyst benzoic acid peroxide and perform ultrasonic emulsification for 10 minutes to obtain a negative electrode active material mixture; then pour the negative electrode active material mixture into a three-necked flask, and polymerize it at 80°C and argon (Ar) atmosphere for 4 hours to obtain a negative electrode active material, wherein the negative electrode active material is artificial graphite and the coating layer is polymethyl methacrylate (PMMA).

[0153] 1.12) Preparation of negative electrode sheets: The negative electrode active material, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are mixed in a proper amount of deionized water solvent system in a weight ratio of 97.5%:0.7%:1.8%:1% to obtain the negative electrode active material. The negative electrode active material is coated on Cu foil, and then dried, cold pressed, and cut to obtain the negative electrode sheet.

[0154] 1.2) Preparation of positive electrode sheet: The positive electrode active material lithium iron phosphate LiFePO4, the conductive agent carbon nanotube (CNT), and the binder polyvinylidene fluoride (PVDF) are dissolved in the solvent N-methylpyrrolidone (NMP) at a weight ratio of 96%:2%:2%, and the positive electrode active material is prepared after being fully stirred and mixed. The positive electrode active material is coated on Al foil, and then dried, cold pressed, and cut to obtain a positive electrode sheet.

[0155] 1.3). Preparation of diaphragm: PE porous polymer film is used as the isolation membrane.

[0156] 1.4). Electrolyte: Dissolve EC / EMC / DMC in 1M LiPF6 at a volume ratio of 1:1:1 and stir evenly.

[0157] 1.5) Assembly: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is in the middle of the positive and negative electrodes to play a role of isolation, and wind them to get the electrode assembly, and add electrolyte. Then hot press at 100℃ and 250MPa for 2min to get the lithium-ion battery.

[0158] In the lithium ion battery of Example 1, the coating material is methyl methacrylate, the coating layer is polymethyl methacrylate, the coating layer thickness is 20 nm, the mass ratio of the coating material to the negative electrode active material is 3, the treatment time is 4 h, the treatment temperature is 80°C, the coating layer molecular weight is 1530000, and the catalyst is benzoic acid peroxide.

[0159] [Example 2]

[0160] The lithium ion battery of Example 2 is substantially the same as the lithium ion battery of Example 1, except that in the lithium ion battery of Example 2, the mass ratio of the coating material to the negative electrode active material is 1, and the thickness of the coating layer is 5 nm.

[0161] [Example 3]

[0162] The lithium ion battery of Example 3 is substantially the same as the lithium ion battery of Example 1, except that in the lithium ion battery of Example 3, the mass ratio of the coating material to the negative electrode active material is 5, and the thickness of the coating layer is 50 nm.

[0163] [Example 4]

[0164] The lithium ion battery of Example 4 is substantially the same as the lithium ion battery of Example 1, except that in the lithium ion battery of Example 4, the mass ratio of the coating material to the negative electrode active material is 1.5, and the thickness of the coating layer is 10 nm.

[0165] [Example 5]

[0166] The lithium ion battery of Example 5 is substantially the same as the lithium ion battery of Example 1, except that in the lithium ion battery of Example 5, the mass ratio of the coating material to the negative electrode active material is 4, and the thickness of the coating layer is 30 nm.

[0167] [Example 6]

[0168] The lithium ion battery of Example 6 is substantially the same as the lithium ion battery of Example 1, except that, in the lithium ion battery of Example 6, the treatment time is 1 h and the coating thickness is 2 nm.

[0169] [Example 7]

[0170] The lithium ion battery of Example 7 is substantially the same as the lithium ion battery of Example 1, except that, in the lithium ion battery of Example 7, the treatment time is 8 h and the coating layer thickness is 60 nm.

[0171] [Example 8]

[0172] The lithium ion battery of Example 8 is substantially the same as the lithium ion battery of Example 1, except that, in the lithium ion battery of Example 8, the treatment time is 3 h and the coating layer thickness is 12 nm.

[0173] [Example 9]

[0174] The lithium ion battery of Example 9 is substantially the same as the lithium ion battery of Example 1, except that, in the lithium ion battery of Example 9, the treatment time is 5 h and the coating layer thickness is 45 nm.

[0175] [Example 10]

[0176] The lithium ion battery of Example 10 is substantially the same as the lithium ion battery of Example 1, except that, in the lithium ion battery of Example 10, the processing temperature is 60° C. and the coating layer thickness is 11 nm.

[0177] [Example 11]

[0178] The lithium ion battery of Example 11 is basically the same as the lithium ion battery in Example 1, except that, in the lithium ion battery of Example 11, the coating material is sodium maleate, and the sodium maleate is directly mixed with the negative electrode active material to obtain a negative electrode active material having a coating layer of sodium maleate; wherein the coating layer thickness is 28 nm, the mass ratio of the coating material to the negative electrode active material is 4.5, and the processing temperature is 60°C.

[0179] [Example 12]

[0180] The lithium ion battery of Example 12 is substantially the same as the lithium ion battery of Example 11, except that, in the lithium ion battery of Example 12, the coating layer thickness is 13 nm, and the mass ratio of the coating material to the negative electrode active material is 2.5.

[0181] [Example 13]

[0182] The lithium ion battery of Example 13 is substantially the same as the lithium ion battery of Example 11, except that, in the lithium ion battery of Example 13, the coating layer thickness is 10 nm, and the mass ratio of the coating material to the negative electrode active material is 2.

[0183] [Example 14]

[0184] The lithium ion battery of Example 14 is substantially the same as the lithium ion battery of Example 11, except that, in the lithium ion battery of Example 14, the coating layer thickness is 5 nm, and the mass ratio of the coating material to the negative electrode active material is 1.

[0185] [Example 15]

[0186] The lithium ion battery of Example 15 is basically the same as the lithium ion battery in Example 1, except that, in the lithium ion battery of Example 15, the coating material is oleic acid diethanolamide borate, and oleic acid diethanolamide borate is directly mixed with the negative electrode active material to obtain a negative electrode active material whose coating layer is oleic acid diethanolamide borate; wherein the coating layer thickness is 10 nm, the mass ratio of the coating material to the negative electrode active material is 1, and the processing temperature is 40°C.

[0187] [Example 16]

[0188] The lithium ion battery of Example 16 is substantially the same as the lithium ion battery of Example 1, except that, in the lithium ion battery of Example 16, the catalyst is peroxyketal.

[0189] [Example 17]

[0190] The lithium ion battery of Example 17 is substantially the same as the lithium ion battery of Example 1, except that, in the lithium ion battery of Example 17, the negative electrode active material is SiO2@Si@C.

[0191] [Comparative Example 1]

[0192] The lithium ion battery of Comparative Example 1 is substantially the same as the lithium ion battery of Example 1, except that, in the lithium ion battery of Comparative Example 1, the negative electrode active material only includes negative electrode active material, ie, graphite.

[0193] [Comparative Example 2]

[0194] The lithium ion battery of Comparative Example 2 is substantially the same as the lithium ion battery of Example 1, except that, in the lithium ion battery of Comparative Example 2, the negative electrode active material only includes SiO2-Si-C negative electrode active material.

[0195] [Comparative Example 3]

[0196] The lithium ion battery of Comparative Example 3 is substantially the same as the lithium ion battery of Example 1, except that, in the lithium ion battery of Comparative Example 3, the coating layer is aluminum oxide (Al2O3).

[0197] [Comparative Example 4]

[0198] The lithium ion battery of Comparative Example 4 is substantially the same as the lithium ion battery of Example 1, except that, in the lithium ion battery of Comparative Example 4, the coating layer is 3(3-nitrophenyl)acrylonitrile / olefin sulfonic acid copolymer.

[0199] 2). Physical characterization of negative electrode active materials

[0200] 2.1) Coating thickness measurement: directly observe and measure through scanning electron microscope (SEM) or transmission electron microscope (TEM).

[0201] 2.2) Molecular weight measurement: Directly measure using a light scattering detector.

[0202] Table 1 Specific experimental parameters of Examples 1-17 and Comparative Examples 1-4

[0203]

[0204]

[0205] 3). Lithium-ion battery performance characterization

[0206] 3.1) Capacity retention rate test: Use the Blue Power test system to perform charge and discharge tests on the battery.

[0207] At 45°C, keep the battery charge and discharge voltage range at 2.5-3.65V, cycle at 1C current density, and record the battery capacity retention rate after 1000 cycles. The test results are shown in Table 2.

[0208] 3.2) Measurement of the first cycle coulombic efficiency: Use the Blue Electric test system to perform charge and discharge tests on the battery.

[0209] At 45°C, the battery charge and discharge voltage range was maintained at 2.5-3.65V, and the battery was cycled at a current density of 1C. The charge and discharge capacity of the battery in the third cycle was recorded, and the capacity ratio of discharge to charge was calculated. The test results are shown in Table 2. (It should be noted here that the first cycle of the battery is the formation stage, and the third cycle is more stable than the second cycle, so the third cycle is selected as the first cycle in the actual sense of this application)

[0210] Table 2 Performance parameters of Examples 1-17 and Comparative Examples 1-4

[0211] Group First-cycle Coulomb efficiency Capacity retention rate Example 1 91.3% 92.3% Example 2 84.0% 88.2% Example 3 83.5% 87.5% Example 4 89.8% 91.5% Example 5 88.1% 91.0% Example 6 82.4% 88.0% Example 7 82.1% 85.3% Example 8 90.1% 90.8% Example 9 84.0% 87.9% Example 10 89.7% 91.3% Embodiment 11 85.6% 86.7% Example 12 88.7% 88.5% Embodiment 13 90% 90.3% Embodiment 14 83% 84.2% Embodiment 15 86.1% 86.1% Example 16 91.3% 92.3% Embodiment 17 78% 77% Comparative Example 1 80% 81% Comparative Example 2 74% 70% Comparative Example 3 82% 83.20% Comparative Example 4 83.0% 82.60%

[0212] The embodiment of the present application uses the capacity retention rate to characterize the cycle performance of the battery. When the capacity retention rate is higher, it means that the capacity of the battery is retained higher after a certain number of cycles, that is, the cycle performance of the battery is better.

[0213] According to Examples 1-17 and Comparative Examples 1-4, coating the surface of the negative electrode active material with at least one of polymethyl methacrylate, sodium maleate and oleic acid diethanolamide borate can improve the first cycle coulombic efficiency and cycle performance of the battery.

[0214] According to Examples 1-10, by making the thickness of the coating layer 5nm-50nm, the first-cycle coulombic efficiency and cycle performance of the battery can be improved; further, making the thickness of the coating layer 10nm-20nm helps to further improve the cycle performance and first-cycle coulombic efficiency of the battery.

[0215] According to Examples 1-10, when the coating layer is polymethyl methacrylate, the molecular weight of the coating layer is 500,000-2,000,000, especially 1,000,000-1,500,000, which helps to further improve the cycle performance and the first-cycle coulombic efficiency of the battery.

[0216] According to Examples 1-5, when the coating material is methyl methacrylate and the coating layer formed is polymethyl methacrylate, the mass ratio of methyl methacrylate to the negative electrode active material is 1-5, especially 1.5-3, which can make the coating layer have a more suitable thickness, and help to further improve the cycle performance and first-cycle coulomb efficiency of the battery.

[0217] According to Examples 6-10, when the coating material is methyl methacrylate and the formed coating layer is polymethyl methacrylate, a treatment time of 1 h-8 h, especially 3 h-5 h, helps to further improve the cycle performance and first-cycle coulombic efficiency of the battery.

[0218] According to Examples 1 and 10, when the coating material is methyl methacrylate and the formed coating layer is polymethyl methacrylate, the processing temperature is not less than 60° C., which can further improve the cycle performance and the first-cycle coulombic efficiency of the battery.

[0219] According to Examples 1, 11-14 and 15, coating the surface of the negative electrode active material with polymethyl methacrylate, sodium maleate or oleic acid diethanolamide borate can improve the performance of the battery.

[0220] According to Examples 11-14, when the coating layer is sodium maleate, the mass ratio of sodium maleate to the negative electrode active material is 1-3, especially 1.5-2, which can improve the cycle performance and the first-cycle coulomb efficiency of the battery.

[0221] It can be seen from Examples 1 and 16 that a variety of catalysts are suitable for the technical solution of the present application.

[0222] It can be seen from Examples 1 and 17 that a variety of negative electrode active materials are suitable for the technical solution of the present application.

[0223] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A negative electrode active material, It is characterized in that include: A negative electrode active material and a coating layer, wherein the coating layer is coated on the surface of the negative electrode active material, and the coating layer comprises at least one of polymethyl methacrylate, sodium maleate and oleic acid diethanolamide borate.

2. The negative electrode active material according to claim 1, It is characterized in that The coating layer has a thickness of 5nm-50nm. Optionally, the coating layer has a thickness of 10nm-20nm.

3. The negative electrode active material according to claim 1 or 2, It is characterized in that The molecular weight of the polymethyl methacrylate is 500,000-2,000,000. Optionally, the molecular weight of the polymethyl methacrylate is 1,000,000-1,500,000.

4. The negative electrode active material according to any one of claims 1 to 3, It is characterized in that The negative electrode active material includes at least one of graphite and silicon-based materials. Optionally, the silicon-based material includes at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon compounds, and composites of elemental silicon, silicon-oxygen compounds, and silicon-carbon compounds; Optionally, the silicon oxide compound includes Si a O b , where a=1, 1≤b≤2; Optionally, the silicon carbon compound comprises Si c C d , where c=1, d=1.

5. A method for preparing a negative electrode active material, It is characterized in that include: Providing negative electrode active material and coating material; The negative electrode active material and the coating material are mixed and treated to obtain the negative electrode active material and a coating layer coated on the surface of the negative electrode active material; Wherein, the coating material includes at least one of methyl methacrylate, sodium maleate and oleic acid diethanolamide borate.

6. The preparation method according to claim 5, It is characterized in that include: The coating layer has a thickness of 5nm-50nm. Optionally, the coating layer has a thickness of 10nm-20nm.

7. The preparation method according to claim 5 or 6, It is characterized in that The negative electrode active material and the coating material are mixed, and the treatment comprises: The methyl methacrylate is polymerized to form the coating layer, and the coating layer includes polymethyl methacrylate; Wherein, the molecular weight of the polymethyl methacrylate is 500,000-2,000,000. Optionally, the molecular weight of the polymethyl methacrylate is 1,000,000-1,500,000.

8. The preparation method according to claim 7, It is characterized in that The mass ratio of the methyl methacrylate to the negative electrode active material is 1-5. Optionally, the mass ratio of the methyl methacrylate to the negative electrode active material is 1.5-3.

9. The preparation method according to claim 7 or 8, It is characterized in that The treatment temperature of the negative electrode active material and the methyl methacrylate is not less than 60°C. Optionally, the treatment temperature is 60°C-220°C.

10. The preparation method according to any one of claims 7 to 9, It is characterized in that The treatment time of the negative electrode active material and the methyl methacrylate is 1 hour to 8 hours. Optionally, the treatment time is 3 hours to 5 hours.

11. The preparation method according to any one of claims 5 to 10, It is characterized in that The negative electrode active material and the coating material are mixed and processed, including: mixing the catalyst, the negative electrode active material and the methyl methacrylate; Optionally, the catalyst comprises at least one of an organic peroxide and an azo compound.

12. The preparation method according to claim 5, It is characterized in that The negative electrode active material and the coating material are mixed and processed, including: The coating material includes at least one of sodium maleate and oleic acid diethanolamide borate; The treatment temperature of the negative electrode active material and at least one of the sodium maleate and oleic acid diethanolamide borate is not less than 40°C. Optionally, the treatment temperature is 40°C-120°C.

13. The preparation method according to claim 12, It is characterized in that The mass ratio of at least one of the sodium maleate and the oleic acid diethanolamide borate to the negative electrode active material is 1-3. Optionally, the mass ratio of at least one of the sodium maleate and the oleic acid diethanolamide borate to the negative electrode active material is 1-2.

14. The preparation method according to any one of claims 5 to 13, It is characterized in that The negative electrode active material includes at least one of graphite and silicon-based materials. Optionally, the silicon-based material includes at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon compounds, silicon-nitrogen compounds, and composites of elemental silicon, silicon-oxygen compounds, and silicon-carbon compounds; Optionally, the silicon oxide compound includes Si a O b , where a=1, 1≤b≤2; Optionally, the silicon carbon compound comprises Si c C d , where c=1, d=1.

15. A negative electrode sheet, It is characterized in that The invention comprises the negative electrode active material according to any one of claims 1 to 4, and / or the negative electrode active material prepared by the method for preparing the negative electrode active material according to any one of claims 5 to 14.

16. A battery cell, It is characterized in that Including the negative electrode sheet as described in claim 15.

17. A battery, It is characterized in that Comprising a battery cell as claimed in claim 16.

18. An electrical device, It is characterized in that Comprising the battery of claim 17.

Citation Information

Patent Citations

  • Negative electrode active material and battery

    CN111146410A

  • Secondary battery

    CN112420998A

  • Negative pole piece and preparation method thereof, secondary battery, battery module, battery pack and power utilization device

    CN115842094A

  • Negative electrode additive, secondary battery, battery module, battery pack and device

    WO2021057305A1

  • Pole piece and lithium ion battery

    WO2023093576A1

Cited By

  • Modified lithium ion battery negative electrode material as well as preparation method and application thereof

    CN119725484A

  • Negative electrode active material and preparation method therefor, and related device

    EP4654289A1